PERILAKU RELIGIUS MAHASISWA PECANDU ALKOHOL - Fahrurrazi Fahrurrazi (Potret Pemikiran, 2020)
ABSTRACTThis paper departs from the unique phenomenon that is experienced by students as alcoholics. The rise of the consumer of alcohol among the students damage the image of the campus it self. Alcohol consumption is deviant behavior. Not only that, alcohol can also eliminate the religiosity of a person. But not for the students, as people who are educated and understand the dangers of alokohol. Pleased with this, it is important to study related to forms of religious conduct student alcohol addict as well as the factors that cause the students still consume alcohol although active in the religious practices and social. This research uses qualitative approaches are phenomenology, where the source of the research consists of five people who have the status as students at several campuses in Yogyakarta. Interview and observation as methods of data collection, while data analysis was done in three stages, namely data reduction, data presentation and data verification. The results showed that students with addictions alcoholics have the attitude of a good religious relationship with God and fellow human beings, such as praying, fasting, helping people in need and participate in community social activities. As for the reasons of students as individuals who are alcoholics, but still internalize religious values and the social in everyday life is because of views and his intentions in taking the alcohol it self. If consuming alcohol because it has become a custom or as a step to calm your self and forget about the problem then it will never bring up the of negative or evil actions.Keywords: The behavior of the religious; Alcohol; Students ABSTRAKTulisan ini berangkat dari fenomena unik yang dialami oleh mahasiswa yakni sebagai pecandu alkohol. Maraknya konsumen alkohol di kalangan mahasiswa merusak citra kampus itu sendiri. Mengonsumsi alkohol merupakan perilaku menyimpang. Tidak hanya itu, alkohol juga dapat menghilangkan religiusitas seseorang. Namun tidak untuk mahasiswa, sebagai orang yang berpendidikan dan paham akan bahaya alokohol. Berkenan dengan hal tersebut, maka penting untuk dikaji terkait dengan bentuk-bentuk perilaku religius mahasiswa pecandu alkohol serta faktor-faktor penyebab mahasiswa tetap mengonsumsi alkohol meskipun aktif dalam praktek-praktek keagamaan dan sosial. Penelitian ini menggunakan pendekatan kualitatif bersifat fenomenologi, dimana sumber penelitian terdiri dari lima orang yang berstatus sebagai mahasiswa di beberapa kampus di Yogyakarta. Wawancara dan observasi sebagai metode pengumpulan data, sedangkan analisis data dilakukan dengan tiga tahap, yakni reduksi data, penyajian data dan verifikasi data. Hasil penelitian menunjukkan bahwa mahasiswa dengan adiksi pecandu alkohol memiliki sikap religius baik hubungannya dengan Tuhan maupun sesama manusia, seperti shalat, puasa, membantu orang yang membutuhkan dan ikut serta dalam kegiatan sosial masyarakat. Adapun alasan mahasiswa sebagai individu yang pecandu alkohol, namun tetap menginternalisasikan nilai-nilai religius dan sosial dalam kehidupan sehari-hari adalah karena pandangan dan niatnya dalam mengonsumsi alkohol itu sendiri. Jika mengonsumsi alkohol karena sudah menjadi adat atau sebagai langkah untuk menenangkan diri dan melupakan masalah maka tidak akan pernah memunculkan perilak negatif atau tindakan kejahatan.Kata kunci: Perilaku religius; Alkohol; Mahasiswa